A clinical case of secondary breast augmentation after previous implants removal - Panchuk, O.; Donets, I.; Galperin, K. (General Surgery, 2024)
The patient underwent primary breast augmentation at a different clinic. Two years later, the implants were replaced with larger breast implants (500 ml each). Three months after the procedure, inflammation of the right and left mammary glands occurred, which led to the removal of both implants. The patient was 24 years old when the surgery took place. She underwent a preoperative examination in accordance with the standards set by the Ministry of Health of Ukraine. The patient came to us for breast augmentation, correction of mammary gland contour imperfections, and management of postoperative scars. Round‑shaped and moderate‑profile implants were selected. Implant parameters: width 13 cm, projection 4.4 cm, implant texture — microtexture, volume 400 ml. We placed the implants in the retropectoral space, and used the dual‑plane method for cavity formation. The surgical procedure lasted for a total of 140 minutes. The duration of the patient’s hospitalisation was one day. No drains were used. The scars on the abdomen were also corrected and fixed in the projection of the inframammary fold. No complications occurred in the postoperative period. The patient received antibiotic therapy and took nonsteroidal anti‑inflammatory drugs. Postoperative wound management was carried out. We prescribed compression underwear for the patient to wear for two months after surgery. Mammoplasty is a commonly performed procedure in plastic surgery. It aims to produce predictable and agreed‑upon aesthetic outcomes for the patient while maintaining a low rate of complications by adhering to modern surgical standards. The patient experienced complications that led to a significant scarring process. The pectoralis major muscle had a significant deformity, and the tissue showed scarring. The lack of muscle elasticity complicated the implant placement, leading to specific challenges throughout the operation. The occurence of complications following mammoplasty invariably has a lasting impact on the capsule’s formation and increases the risk of developing both early and late postoperative issues.